2013
DOI: 10.3171/2013.6.jns122319
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of glutamate transporter GLT-1 in peritumoral tissue associated with prolonged survival and decreases in tumor growth in a rat model of experimental malignant glioma

Abstract: Object Gliomas are known to release excessive amounts of glutamate, inducing glutamate excitotoxic cell death in the peritumoral region and allowing the tumor to grow and to expand. Glutamate transporter upregulation has been shown to be neuroprotective by removing extracellular glutamate in a number of preclinical animal models of neurodegenerative diseases, including amyotrophic lateral sclerosis and Parkinson disease as well as psychiatric disorders such as depression. The authors therefore hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…[ 43 ] Sattler and colleagues have recently demonstrated that thiamphenicol, through its upregulation of EAAT2 in peritumoural tissue, may be similarly beneficial. [ 44 ] PPARγ agonists may constitute an additional agent that activates glutamate transport within tumour cells and peritumourally. These agents could be considered for adjunct treatment in current regimens and in combination therapy for dual mechanistic efficacy in sub therapeutic doses to avoid associated adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] Sattler and colleagues have recently demonstrated that thiamphenicol, through its upregulation of EAAT2 in peritumoural tissue, may be similarly beneficial. [ 44 ] PPARγ agonists may constitute an additional agent that activates glutamate transport within tumour cells and peritumourally. These agents could be considered for adjunct treatment in current regimens and in combination therapy for dual mechanistic efficacy in sub therapeutic doses to avoid associated adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In brain tumors, astrocytes sustain glioma growth and invasion, exacerbating neuroinflammation 12 . In the early stages of glioma, astrocytes protect neurons by controlling the uptake of glutamate released by tumor cells 13 , however, as the tumor grows, astrocytes lose their protective role and, in fact, overexpression of GLT-1 prolongs survival in animal models of malignant glioma 14 .…”
Section: Introductionmentioning
confidence: 99%
“…These results mean that the use of adenosine triphosphate (ATP) competitive inhibitors to treat glioma will be less efficient [191]. In addition, increased expression of glutamate transporters, also known as excitatory amino-acid transporters, leads to prolonged survival and reduced tumor growth in glioma-bearing animals [192]. Further, PKC is involved in the activation and redistribution of glutamate transporters [183,193,194].…”
Section: Gastrointestinal Stromal Tumormentioning
confidence: 99%